2012
DOI: 10.1111/j.1365-2036.2012.05220.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: faecal microbiota transplantation in the management of inflammatory bowel disease

Abstract: Summary Background The intestinal microbiota is involved in the pathogenesis of inflammatory bowel disease (IBD). Faecal microbiota transplantation (FMT) has been used for the management of IBD as well as infectious diarrhoea. Aim To undertake a systematic review of FMT in patients with IBD. Methods The systematic review followed Cochrane and PRISMA recommendations. Nine electronic databases were searched in addition to hand searching and contacting experts. Inclusion criteria were reports (RCT, nonrandomised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
209
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(221 citation statements)
references
References 58 publications
0
209
0
12
Order By: Relevance
“…Several studies have been published on the use of FMT in IBD [128]. In one study, FMT was administered via enema in a small group of children and young adults [129], and no serious adverse events were reported.…”
Section: Faecal Microbiota Transplantationmentioning
confidence: 99%
“…Several studies have been published on the use of FMT in IBD [128]. In one study, FMT was administered via enema in a small group of children and young adults [129], and no serious adverse events were reported.…”
Section: Faecal Microbiota Transplantationmentioning
confidence: 99%
“…There is increasing interest in the use of faecal microbiota transplantation, which has been undertaken by a small number of institutions for many years, despite little robust research evidence. A recent systematic review failed to identify any controlled trials of faecal microbiota transplantation in Crohn's disease (80) . However, case series/case reports of at least six patients receiving faecal microbiota transplantation for the management of Crohn's disease were identified in which the majority experienced considerable disease response (although outcome data for Crohn's disease and ulcerative colitis were combined) (80) .…”
Section: Crohn's Diseasementioning
confidence: 99%
“…A recent systematic review failed to identify any controlled trials of faecal microbiota transplantation in Crohn's disease (80) . However, case series/case reports of at least six patients receiving faecal microbiota transplantation for the management of Crohn's disease were identified in which the majority experienced considerable disease response (although outcome data for Crohn's disease and ulcerative colitis were combined) (80) . Controlled trials of faecal microbiota transplantation in management of active Crohn's disease are warranted.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…An example is the narrow-spectrum Thuricin CD that is produced by Bacillus thuringiensis and has activity against C. diffile (85) . A meta-analysis including nine reports describing FMT in twenty-six patients with IBD concluded that, although the evidence is limited and weak, the majority of the studies suggest that FMT may be an effective treatment option in IBD (86) . A retrospective analysis of sixty-two patients with UC treated with FMT, reported response to FMT in 91·9 % (fifty-seven/sixty-two) of the patients, of which 67·7 % (forty-two/sixty-two) achieved complete remission and 24·2 % (fifteen/ sixty-two) achieved partial response.…”
Section: Faecal Microbiota Transplantationmentioning
confidence: 99%